Welcome :: Homework Help and Answers :: Mathskey.com
Welcome to Mathskey.com Question & Answers Community. Ask any math/science homework question and receive answers from other members of the community.

13,387 questions

17,804 answers

1,438 comments

37,325 users

Given the explicit formula for a geometric sequence find the first five terms and the 8th term

0 votes
7) a_n = 3^(n − 1)
8) a_n = 2 ⋅ (1/4)^(n − 1)
9) an = −2.5 ⋅ 4^(n − 1)
10) an = −4 ⋅ 3^(n-1)
asked Oct 23, 2018 in ALGEBRA 2 by anonymous

2 Answers

0 votes
7)
a_n  =  3^(n − 1)
a1  =  3^(1 − 1)
      =  3^(0)
      =  1
a2  =  3^(2 − 1)
      =  3^(1)
      =  3
a3  =  3^(3 − 1)
      =  3^(2)
      =  9
a4  =  3^(4 − 1)
      =  3^(3)
      =  27
a5  =  3^(5 − 1)
      =  3^(4)
      =  81
a8  =  3^(8 − 1)
      =  3^(7)
      =  2187
 
8)
a_n  =  2 X (1/4)^(n − 1)
a1  =   2 X (1/4)^(1 − 1)
      =  2 X (1/4)^(0)
      =  2
a2  =   2 X (1/4)^(2 − 1)
      =  2 X (1/4)^(1)
      =  2 X (1/4)
      =  1/2
a3  =   2 X (1/4)^(3 − 1)
      =  2 X (1/4)^(2)
      =  2 X (1/16)
      =  1/8
a4  =   2 X (1/4)^(4 − 1)
      =  2 X (1/4)^(3)
      =  2 X (1/64)
      =  1/32
a5  =   2 X (1/4)^(5 − 1)
      =  2 X (1/4)^(4)
      =  2 X (1/256)
      =  1/128
a8  =   2 X (1/4)^(8 − 1)
      =  2 X (1/4)^(7)
      =  2 X (1/16384)
      =  1/8192
answered Oct 24, 2018 by homeworkhelp Mentor
0 votes

Contd........

9)

an  =  −2.5 ⋅ 4^(n − 1)
a1  =  −2.5 ⋅ 4^(1 − 1)
      =  −2.5 ⋅ 4^(0)
      =  -2.5
a2  =  −2.5 ⋅ 4^(2 − 1)
      =  −2.5 ⋅ 4^(1)
      =  -2.5 X 4
      =  -10
a3  =  −2.5 ⋅ 4^(3 − 1)
      =  −2.5 ⋅ 4^(2)
      =  -2.5 X 16
      =  -40
a4  =  −2.5 ⋅ 4^(4 − 1)
      =  −2.5 ⋅ 4^(3)
      =  -2.5 X 64
      =  -160
a5  =  −2.5 ⋅ 4^(5 − 1)
      =  −2.5 ⋅ 4^(4)
      =  -2.5 X 256
      =  -640
a8  =  −2.5 ⋅ 4^(8 − 1)
      =  −2.5 ⋅ 4^(7)
      =  -2.5 X 16384
      =  -40960
 
10)
an = −4 ⋅ 3^(n-1)
a1  =  -4 X 3^(1 − 1)
      =  -4 X 3^(0)
      =  -4
a2  =  -4 X 3^(2 − 1)
      =  -4 X 3^(1)
      =  -4 X 3
      =  -12
a3  =  -4 X 3^(3 − 1)
      =  -4 X 3^(2)
      =  -4 X 9
      =  - 36
a4  =  -4 X 3^(4 − 1)
      =  -4 X 3^(3)
      =  -4 X 27
      =  -108
a5  =  -4 X 3^(5 − 1)
      =  -4 X 3^(4)
      =  -4 X 81
      =  - 324
a8  =  -4 X 3^(8 − 1)
      =  -4 X 3^(7)
      =  -4 X 2187
      =  - 8748
answered Oct 24, 2018 by homeworkhelp Mentor

Related questions

...